The reflection of the sexual minorities theme in the press of the Republic of Moldova. Between acceptance and discrimination - Victoria BULICANU (Moldoscopie)
The issue of equitable approach to issues related to discrimination against certain social categories in our country remains one of the most discussed in various public events, such as public debates, seminars, trainings, etc. In this context, the press remains one of the key - tools for guiding society, on the correctness in which the issues of discrimination are reflected on the basis of various criteria. The article below seeks to elucidate the way in which one of the most discriminated social groups in this country, such as that of sexual minorities, is approached in journalistic materials. Recently, more and more articles have appeared in the local media, reflecting the situation and problems of this social group, but the way in which journalists manage to present the subject, cannot always be considered in accordance with the deontological aspects of the profession. Thus, we aim to elucidate in the material below, the ways in which the subject of sexual minorities is reflected and the problems they face, the mistakes that journalists make in the process of covering the topic, as well as to offer some recommendations to avoid mistakes, through which the press could also be considered an instrument of manipulation and discrimination in relation to this social category